A Novel 3D-Printed and Miniaturized Periodic Counter Current Chromatography System for Continuous Purification of Monoclonal Antibodies - Carlotta Kortmann; Taieb Habib; Christopher Heuer; Dörte Solle; Janina Bahnemann (Micromachines, 2024)
Continuous chromatography has emerged as one of the most attractive methods for protein purification. Establishing such systems involves installing several chromatographic units in series to enable continuous separation processes and reduce the cost of the production of expensive proteins and biopharmaceuticals (such as monoclonal antibodies). However, most of the established systems are bulky and plagued by high dead volume, which requires further optimization for improved separation procedures. In this article, we present a miniaturized periodic counter-current chromatography (PCCC) system, which is characterized by substantially reduced dead volume when compared to traditional chromatography setups. The PCCC device was fabricated by 3D printing, allowing for flexible design adjustments and rapid prototyping, and has great potential to be used for the screening of optimized chromatography conditions and protocols. The functionality of the 3D-printed device was demonstrated with respect to the capture and polishing steps during a monoclonal antibody purification process. Furthermore, this novel miniaturized system was successfully used for two different chromatography techniques (affinity and ion-exchange chromatography) and two different types of chromatographic units (columns and membrane adsorbers). This demonstrated versability underscores the flexibility of this kind of system and its potential for utilization in various chromatography applications, such as direct product capture from perfusion cell cultures.